Corruption and human rights - Malem-Seña, Jorge F. (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Corruption is a way of acting, an instrument, a too l that allows achieving certain goals otherwise unattainable or more expensive, and democracy has not been a system capable of eliminating its existence. Despite its universality, the different types of corruption have dissimilar etiology and development. This creates some problems for better characterization and understanding of corruption and, of course, for its more effective eradication. Therefore this article presents a definition of corruption clearing the way to avoid bad understood purely verbal. Universality of corruption does not imply that always the same goods or identical rights are affected. In this sense, it is possible to think that sometimes affects human rights, although it does not happen in all cases. There is not a direct or causal relationship between corruption and violation of human rights. The second part of this work is intended for the analysis of the most burdensome consequences that some corrupt practices have for human rights. And, ultimately, there is an analysis of the standard me asures that have been identified to address this human calamity.